Traditional versus optimum power load training in professional cyclists: A randomized controlled trial - Gil-Cabrera, J.; Valenzuela, P. L.; Alejo, L. B.; Talavera, E.; Montalvo-Pérez, A.; Lucia, A.; Barranco-Gil, D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the effectiveness of optimum power load training (OPT, training with an individualized load and repetitions that maximize power output) and traditional resistance training (TRT, same number of repetitions and relative load for all individuals) in professional cyclists. Methods: Participants (19 [1] y, peak oxygen uptake 75.5 [6] mL/kg/min) were randomly assigned to 8 weeks (2 sessions per week) of TRT (n = 11) or OPT (n = 9), during which they maintained their usual cycle training schedule. Training loads were continuously registered, and measures of muscle strength/power (1-repetition maximum and maximum mean propulsive power on the squat, hip thrust, and lunge exercises), body composition (assessed by dual-energy X-ray absorptiometry), and endurance performance (assessed on both an incremental test and an 8-min time trial) were collected before and at the end of the intervention. Results: OPT resulted in a lower average intensity (percentage of 1-repetition maximum) during resistance training sessions for all exercises (P < .01), but no differences were found for overall training loads during resistance or cycling sessions (P > .05). Both programs led to significant improvements in all strength/power-related parameters, muscle mass (with no changes in total body mass but a decreased fat mass), and time-trial performance (all Ps < .05). A trend toward increased power output at the respiratory compensation point was also found (P = .056 and .066 for TRT and OPT, respectively). No between-groups differences were noted for any outcome (P > .05). Conclusion: The addition of either TRT or OPT to an endurance training regimen of elite cyclists results in similar improvements of body composition, muscle strength/power, and endurance performance.